A longitudinal study of risk perceptions and e-cigarette initiation among college students: Interactions with smoking status. (1st May 2018) - Cooper, Maria; Loukas, Alexandra; Case, Kathleen R.; Marti, C. Nathan; Perry, Cheryl L.
Highlights: We examine prospective risk factors of e-cigarette use in college students. Among never users at wave 1, 21% initiated e-cigarette use over the two year period. Lower risk perceptions predicted e-cigarette use for non-smoking college students. Results support need to highlight risks of e-cigarette use in non-smoking students. Abstract: Background: Recent data suggest that lower perceived risks of e-cigarettes are associated with e-cigarette use in young adults; however, the temporality of this relationship is not well-understood. We explore how perceptions of harmfulness and addictiveness of e-cigarettes influence e-cigarette initiation, and specifically whether this association varies by cigarette smoking status, in a longitudinal study of tobacco use on college campuses. Methods: Data are from a 5-wave 24-college study in Texas. Only students who reported never using e-cigarettes at wave 1 were included (n = 2565). Multilevel discrete-time hazard models, accounting for school clustering, were used. The dependent variable, ever e-cigarette use, was assessed at each wave. Both time-varying (e-cigarette perceptions of harmfulness and addictiveness, age, use of cigarettes, use of other tobacco products, and use of other substances) and time-invariant demographic covariates were included. Two-way interactions between each e-cigarette perception variable and current conventional cigarette use were tested to determine if the hypothesized relationship differed among smokers and non-smokers. Results: 21% of all never e-cigarette users at baseline had initiated e-cigarette ever use by wave 5. Significant two-way interactions qualified the relationship between risk perceptions and e-cigarette initiation. Specifically, perceptions of a lower degree of harmfulness ( OR  = 1.13, p  = .047) and addictiveness ( OR  = 1.34, p  < .001) of e-cigarettes predicted initiation among non-smokers, but not among current smokers. Conclusion: Perceiving a lower degree of risk of e-cigarettes contributes to subsequent e-cigarette initiation among non-smokers, but not among current smokers. Findings: have implications for prevention campaigns focusing on the potential harm of e-cigarettes for non-smoking college students.